Islamic legal revival : reception of European law and transformations in Islamic legal thought in Egypt, 1875-1952 - Wood, Leonard G. H. (Leonard Gustauvus Harrison) (Oxford : Oxford University Press, 2016)
Leonard Wood presents his ground breaking history of Islamic revivalist thought in Islamic law. He brings to life the tumultuous history of colonial interventions in Islamic legal consciousness during the nineteenth and early twentieth centuries, and tells the story of the rapid displacement of local Egyptian and Islamic law by transplanted European codes and details the evolution of resultant movements to revive Islamic law.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 26, 2016).
Keywords: Islamic law -- History -- 20th century; Islamic renewal; Law -- Europe -- History -- 20th century; Law